2022
DOI: 10.12669/pjms.38.3.4699
|View full text |Cite
|
Sign up to set email alerts
|

Subtle morpho-functional kidney changes in type-2 diabetes mellitus patients: A duplex ultrasound assessment

Abstract: Objectives: Diabetes mellitus (DM) is a common endocrine disease with serious effects on multiple organs including the kidneys. This study aimed to investigate the subtle effects of type 2 DM (T2DM) on the kidneys. Methods: This was a prospective case-control study conducted in the Radiology Department of University of Science and Technology Hospital (USTH) campus, Sana’a, Republic of Yemen, from 1 January 2020 to 31 November 2020. The renal length (RL), renal width (RW), resistive index (RI), and pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The findings of our study are comparable with a similar study conducted by Dawha et 6,[14][15][16][17] In our study, it was observed that 47.1% of diabetic patients with normal serum creatinine had a high Pulsatility index and 100% of diabetic patients with high serum creatinine had an elevated Pulsatility index. We found out that there was a strong, positive correlation between PI and serum creatinine in the study population, which was found to be statistically significant (r = .817, p<0.001).…”
Section: Figure 2: Distribution Of Study Population According To Resi...supporting
confidence: 92%
See 2 more Smart Citations
“…The findings of our study are comparable with a similar study conducted by Dawha et 6,[14][15][16][17] In our study, it was observed that 47.1% of diabetic patients with normal serum creatinine had a high Pulsatility index and 100% of diabetic patients with high serum creatinine had an elevated Pulsatility index. We found out that there was a strong, positive correlation between PI and serum creatinine in the study population, which was found to be statistically significant (r = .817, p<0.001).…”
Section: Figure 2: Distribution Of Study Population According To Resi...supporting
confidence: 92%
“…The findings in our study were comparable to the study conducted by Alareqi et al, who found a statistically significant correlation between the two parameters. 15 Based on the findings, we can say that better glycaemic control (lower HbA1c) is associated with better renal outcomes as predicted by the Pulsatility index and vice versa. And that in patients with poor glycaemic control (higher HbA1c), the Pulsatility index is higher suggesting poorer renal status.…”
Section: Figure 2: Distribution Of Study Population According To Resi...mentioning
confidence: 86%
See 1 more Smart Citation
“…1 Ultrasonography is a diagnostic imaging technique using ultrasound waves to visualise the body structures, including soft tissues, such as liver, muscles, and blood vessels. 1,2 It is a highly valuable imaging modality in assessing liver parenchyma and detecting liver lesions by providing accurate diagnostic information and detecting complications. 3 It is an ionising radiation free technique, real time, widely available, non-invasive, and low cost.…”
Section: Introductionmentioning
confidence: 99%